2016
DOI: 10.1007/s11661-016-3524-5
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Static Recrystallization with Simultaneous Precipitation and Solute Drag

Abstract: In the present work, we introduce a state parameter-based microstructure evolution model, which incorporates the effect of solute atoms and precipitates on recrystallization kinetics. The model accounts for local precipitate coarsening at grain boundaries, which promotes an average grain boundary movement even if the Zener pinning force exceeds the driving force for recrystallization. The impact of solute drag on the grain boundary mobility as well as simultaneous precipitation is discussed in detail. The mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…This was associated with the higher stability of V-containing precipitates against coarsening, coagulation, or dissolution during high-temperature deformation as compared to Cr-based particles. The pinning effect of V (C, N) precipitates on the moving grain boundaries during recrystallization was noted in [34]. The authors showed that with increasing in V-carbonitride fraction, the plateau on the recrystallization fraction vs. recrystallization time started in earlier times and at higher testing temperatures [34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was associated with the higher stability of V-containing precipitates against coarsening, coagulation, or dissolution during high-temperature deformation as compared to Cr-based particles. The pinning effect of V (C, N) precipitates on the moving grain boundaries during recrystallization was noted in [34]. The authors showed that with increasing in V-carbonitride fraction, the plateau on the recrystallization fraction vs. recrystallization time started in earlier times and at higher testing temperatures [34].…”
Section: Resultsmentioning
confidence: 99%
“…The pinning effect of V (C, N) precipitates on the moving grain boundaries during recrystallization was noted in [34]. The authors showed that with increasing in V-carbonitride fraction, the plateau on the recrystallization fraction vs. recrystallization time started in earlier times and at higher testing temperatures [34]. The positive effect of stable disperse particles was also associated with the fact that they could act as recrystallization nuclei and promote grain refinement [1].…”
Section: Resultsmentioning
confidence: 99%
“…The grain and subgrain boundary mobilities are most important input parameters determining the recrystallization kinetics. To model the HAGB mobility, the same approach is used, which has recently been successfully applied to recrystallization kinetics simulations in micro-alloyed steel [13] with…”
Section: Boundary Mobilitymentioning
confidence: 99%
“…The concentration of Mg, C GB , is assumed to be identical to the matrix concentration. [11,13,29] If the Mg content in the alloy increases, the grain boundary mobility decreases due to the increasing amount of atoms that must be dragged along with the moving boundary. In the limit of zero Mg, the calculated integral mobility approximates the free mobility since the solute drag mobility approaches infinity.…”
Section: Boundary Mobilitymentioning
confidence: 99%
“…It should be noted that M 0 in Eq. [5] corresponds to an effective interface mobility, which accounts for the lattice reconstruction, solute drag effect due to substitutional alloying elements, [32] pinning effects of precipitates at the grain boundary, [33] and the direction of the transformation. [34] The local driving force DG depends on the solute concentrations at the interface.…”
Section: Ferrite Growthmentioning
confidence: 99%